2012
DOI: 10.3389/fnhum.2012.00320
|View full text |Cite
|
Sign up to set email alerts
|

Identifying temporal and causal contributions of neural processes underlying the Implicit Association Test (IAT)

Abstract: The Implicit Association Test (IAT) is a popular behavioral measure that assesses the associative strength between outgroup members and stereotypical and counterstereotypical traits. Less is known, however, about the degree to which the IAT reflects automatic processing. Two studies examined automatic processing contributions to a gender-IAT using a data driven, social neuroscience approach. Performance on congruent (e.g., categorizing male names with synonyms of strength) and incongruent (e.g., categorizing f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 73 publications
1
15
0
Order By: Relevance
“…The second was found in a later mental process, starting around 450 ms after stimulus onset (microstate 6). Thus, in line with previous EEG studies, we found differences between the two IAT conditions in both the first (18)(19)(20)(21) and second half (18,19,(22)(23)(24) of task execution. Adding to previous research, we demonstrated that these differences were due to a longer duration of the same mental Congruent 0 88 88 132 158 224 224 252 252 442 442 612 612 742 742 868 Incongruent 0 88 88 132 156 226 226 260 260 446 446 664 664 826 826 954 processes in the incongruent condition.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The second was found in a later mental process, starting around 450 ms after stimulus onset (microstate 6). Thus, in line with previous EEG studies, we found differences between the two IAT conditions in both the first (18)(19)(20)(21) and second half (18,19,(22)(23)(24) of task execution. Adding to previous research, we demonstrated that these differences were due to a longer duration of the same mental Congruent 0 88 88 132 158 224 224 252 252 442 442 612 612 742 742 868 Incongruent 0 88 88 132 156 226 226 260 260 446 446 664 664 826 826 954 processes in the incongruent condition.…”
Section: Discussionsupporting
confidence: 92%
“…[18][19][20][21] and at late time periods (in the second half of task execution; refs. 18, 19, and 22-24).…”
Section: Significancementioning
confidence: 99%
“…The remaining trials were averaged in a grand average waveform, but also separately for each condition (masculine toy-congruent, masculine toy-incongruent, feminine toy-congruent, feminine toy-incongruent). Following Forbes et al (2012) average waveforms included both correct and incorrect trials, because the improved scoring algorithm to compute a participant's behavioral stereotype score also included error trials. In addition, we did not exclude any trials on the basis of RTs, because all RTs where within an acceptable range (i.e., 400-1100 ms; see Greenwald et al, 2003).…”
Section: Implicit Gender Stereotypesmentioning
confidence: 99%
“…These studies have mainly focused on activation differences between congruent and incongruent IAT conditions. ERP studies have commonly identified differences in both late (Coates & Campbell, 2010;Hurtado, et al, 2009;Williams & Themanson, 2011) and, to a lesser degree, early (Coates & Campbell, 2010;Forbes et al, 2012;Ibáñez et al, 2010) ERP components as a function of IAT condition. fMRI studies have emphasized an important role of activations in the dorsolateral and ventrolateral prefrontal cortex, as well as in the anterior cingulate cortex, in the control processes that are needed to override the implicit associations in order to correctly perform the IAT on incongruent trials (Chee et al, 2000;Knutson et al, 2007;Luo et al, 2006).…”
mentioning
confidence: 99%